Differential FDG-PET Uptake Patterns in Uninfected and Infected Central Prosthetic Vascular Grafts. Issue 3 (September 2015) - Berger, P.; Vaartjes, I.; Scholtens, A.; Moll, F.L.; De Borst, G.J.; De Keizer, B.; Bots, M.L.; Blankensteijn, J.D.
Abstract : Objective: 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) scanning has been suggested as a means to detect vascular graft infections. However, little is known about the typical FDG uptake patterns associated with synthetic vascular graft implantation. The aim of the present study was to compare uninfected and infected central vascular grafts in terms of various parameters used to interpret PET images. Methods: From 2007 through 2013, patients in whom a FDG-PET scan was performed for any indication after open or endovascular central arterial prosthetic reconstruction were identified. Graft infection was defined as the presence of clinical or biochemical signs of graft infection with positive cultures or based on a combination of clinical, biochemical, and imaging parameters (other than PET scan data). All other grafts were deemed uninfected. PET images were analyzed using maximum systemic uptake value (SUVmax), tissue to background ratio (TBR), visual grading scale (VGS), and focality of FDG uptake (focal or homogenous). Results: Twenty-seven uninfected and 32 infected grafts were identified. Median SUVmax was 3.3 (interquartile range [IQR] 2.0–4.2) for the uninfected grafts and 5.7 for the infected grafts (IQR 2.2–7.8). Mean TBR was 2.0 (IQR 1.4–2.5) and 3.2 (IQR 1.5–3.5), respectively. On VGS, 44% of the uninfected and 72% of the infected grafts were judged as a high probability for infection. Homogenous FDG uptake was noted in 74% of the uninfected and 31% of the infected grafts. Uptake patterns of uninfected and infected grafts showed a large overlap for all parameters. Conclusion: The patterns of FDG uptake for uninfected vascular grafts largely overlap with those of infected vascular grafts. This questions the value of these individual FDG-PET-CT parameters in identifying infected grafts.